Untangling sporadic brain arteriovenous malformations: towards targeting the KRAS/MAPK pathway - Jabarkheel, Rashad; Li, Lun; Frankfurter, Maxwell; Zhang, Daniel Y.; Gajjar, Avi; Muhammad, Najib; Srinivasan, Visish M.; Burkhardt, Jan-Karl; Kahn, Mark (Frontiers in Surgery, 2024)
Brain arteriovenous malformations (AVMs) are vascular lesions characterized by abnormal connections between parenchymal arteries and veins, bypassing a capillary bed, and forming a nidus. Brain AVMs are consequential as they are prone to rupture and associated with significant morbidity. They can broadly be subdivided into hereditary vs. sporadic lesions with sporadic brain AVMs representing the majority of all brain AVMs. However, little had been known about the pathogenesis of sporadic brain AVMs until the landmark discovery in 2018 that the majority of sporadic brain AVMs carry somatic activating mutations of the oncogene, Kirsten rat sarcoma viral oncogene homologue (KRAS), in their endothelial cells. Here, we review the history of brain AVMs, their treatments, and recent advances in uncovering the pathogenesis of sporadic brain AVMs. We specifically focus on the latest studies suggesting that pharmacologically targeting the KRAS/MEK pathway may be a potentially efficacious treatment for sporadic brain AVMs.